Web-based e-learning systems acceptance and success: a review of contributing factors from the instructors’ perception - Oyefolahan, Ishaq Oyebisi; Abdallah, Nahel A O (IEEE, 2014)
Web-based e-learning systems turn out to be one of the most significant innovations for educational delivery and have emerged as an imperative paradigm of modern education system. Characterized by non-restriction in time and place, it is offering new possibilities to higher education institutions to be able to provide flexible and cost effective distance learning environment. While substantial numbers of studies and researches have been conducted on e-learning systems, few researches have investigated instructors’ perspectives as a major determinant of success in the implementation of such systems. Despite the reported high by-ins into corporate investment in e-learning systems, surveys have shown high rate of failure, with the intention to use such systems being very low and instructors intention to use the systems as against the traditional approach still shows wide margin. Against this background, this paper attempts to fill the gap in the current body of knowledge by reviewing and identifying critical success factors that are likely to play significant roles in instructors’ acceptance and sustained use of web-based e-learning systems in higher educational context. Understanding the nature of these factors may help universities in developed countries to endorse the use of e-learning systems for teaching and learning processes.